Kinematics of the diffuse intragroup and intracluster light in groups and clusters of galaxies in the local universe within 100 Mpc distance - Arnaboldi, Magda; Gerhard, Ortwin (Frontiers in Astronomy and Space Sciences, 2022)
Nearly all intragroup (IGL) and intracluster light (ICL) comes from stars that are not bound to any single galaxy but were formed in galaxies and later unbound from them. In this review we focus on the physical properties - phase space distribution, metallicity and age - of the ICL and IGL component of the clusters/groups in the local universe, within 100 Mpc distance. Kinematic information on these very low surface brightness structures mostly comes from discrete tracers such as planetary nebulae and globular clusters, showing highly unrelaxed velocity distributions. Cosmological hydrodynamical simulations provide key predictions for the dynamical state of IGL and ICL and find that most IC stars are dissolved from galaxies that subsequently merge with the central galaxy. The increase of the measured velocity dispersion with radius in the outer halos of bright galaxies is a key feature to identify IGL and ICL components. In the local groups and clusters, IGL and ICL are more centrally concentrated than the galaxies, their typical fractions are few to ten percent, i.e. significantly lower than the average values in more evolved clusters, and mostly consist of old (10 Gyr) and metal-poor stars ([M/Fe]<-1.0) stars. The new imaging facility, like LSST and Euclid, and the ``big eyes’’ on the sky - ELT and JWST with their advanced instrumentation -promise to greatly increase information on the satellite progenitors of the ICL, their ages, metal content, masses, and evolution and, thereby, our understanding of this enigmatic component.